REKAYASA PINTU GESER OTOMATIS DENGAN MENGGUNAKAN SENSOR PASSIVE INFRA RED (PIR) - Syamsudin Nur Wahid; Eko Suprayitno (Universitas Islam Balitar Blitar, 2020)
Along with the rapid development of the times, in everyday life in the field of technology. This has encouraged humans to create and innovate in the field of technology to create a tool that can facilitate human activities. The door is something that is insulated inside the house and outside the home. The door in general as access into and out of the house or outside the home. Generally the door is opened manually by sliding because opening and closing the door does not take up much space for the mechanism of opening and closing the door so that most doors are opened with a manual mechanism. Current technological developments have also affected the door open and close system so that the door can be opened and closed automatically by using the Passive Infra Red Sensor (PIR).This simulation tool consists of a DC motor controller circuit and a sensor that is regulated by a microcontroller system with the input sensor. In a DC motor controller circuit, the direction of rotation and speed is regulated by the motor driver. As for the sensor circuit, it is used as a motion detector. For the microcontroller as a controller, selected from the type of Arduino Uno with Arduino programming. In the process of control, the sliding door will move to open and close the door either or not move according to PIR sensor input. The control system that is designed here only uses two commands at regular intervals in a single program execution, both the calling and the intended purpose of the user.